The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.9790/0853-1606124951
|View full text |Cite
|
Sign up to set email alerts
|

Stamp technique -New perspective of Aesthetic Dentistry : A Case Report

Abstract: "Stamp technique" is a new technique for restoring class I and class II restorations with accurate occlusal topography. It was introduced mainly to restore Class I cavities and erosively damaged teeth. This technique is possible in teeth where preoperative anatomy of the tooth is intact and not destructed by carious lesion. A precise tooth-like restoration with an accurate functional occlusion is obtained when the stamp technique is perfomed. This technique is also utilized for class II cavity restorations whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 2 publications
(3 reference statements)
0
6
0
1
Order By: Relevance
“…Cling film can be used instead of Teflon tape since it does not need to be removed during curing. It also shields composite materials from numerous exposures to ambient light [5].…”
Section: Discussionmentioning
confidence: 99%
“…Cling film can be used instead of Teflon tape since it does not need to be removed during curing. It also shields composite materials from numerous exposures to ambient light [5].…”
Section: Discussionmentioning
confidence: 99%
“…In the stamp process, the final composite increment is put against the fabricated occlusal matrix, which replicates the original occlusal morphology of the posterior teeth, and then the composite is cured. The stamp's pressure on the composite resin reduces the creation of microbubbles and oxygen's interference with the final layer's curing, both of which are important long-term success factors (14). According to Geena Mary et al, the microbrush stamp technique is a simple process for accurately recreating occlusal topography in teeth with nearly intact occlusal anatomy (7).…”
Section: Discussionmentioning
confidence: 99%
“…The pressure exerted by the stamp on the composite resin decreases the formation of microbubbles as well as interference of oxygen in the curing of the last layer which are considered for long-term success factors. 9 Geena Mary et al concluded microbrush stamp technique is an easy to follow procedure to effectively and efficiently recreate occlusal topography in teeth with almost intact occlusal anatomy. 2 Alexy Murashkin proposed different stamp technique and concluded it to be a convenient, favorable and biomimetic procedure.…”
Section: Discussionmentioning
confidence: 99%